EVALUASI PERESEPAN FORMULARIUM DI APOTEK RAWAT JALAN RSUD TAMAN HUSADA BONTANG PERIODE APRIL - JUNI TAHUN 2023 - Muhammad Evan,; Adhe Septa Ryant Agus,; Raymon Simanullang, (Journal of Innovation Research and Knowledge, 2025)
Hospitals must follow the National Formulary when prescribing drugs. According to the National Formulary, the percentage of drug prescriptions in hospitals is at least 80%, according to the standard indicator of health service quality number 30 of 2022 concerning hospital prescriptions. One of the class B hospitals in East Kalimantan Province, Taman Husada Bontang General Hospital treats patients with National Health Insurance (JKN), whose population continues to grow. The purpose of this study was to assess the suitability of Bontang Regional Hospital to prescribe drugs in 2023 according to the National Formulary. Retrospective data collection was used in an observational study design. Based on the inclusion and exclusion criteria, the study sample consisted of all prescription sheets for outpatients at Bontang Regional Hospital from April to June 2023. Prescription forms, drug content, dosage strength, and dosage form are indicators of suitability for prescribing. By comparing the number of drug prescriptions written according to the National Formulary with the total number of prescriptions, the percentage of suitability was calculated. According to the National Formulary, 98.23% of drug items matched, and 99.76% of prescription sheets also matched. Bontang Regional Hospital's prescription is not 100% in accordance with the National Formulary, but based on drug items and prescriptions, it has exceeded the standard indicators of drug prescriptions in hospitals (more than 80%).